PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIS SISWA KELAS IV SDN 044/VIII TELUK SINGKAWANG - Natasya Khairunisa; Suci Rahma Putri; Martiya Nurni Khairita (STKIP Subang, 2023)
The purpose of this study is to be able to determine the effect of the problem-based learning model on the mathematical learning outcomes of fourth grade students, especially in equivalent fraction material. The background problem in this study is the low mathematics learning outcomes of class IV SDN 044/VIII Teluk Singkawang. The effort to overcome this problem is by applying a problem-based learning model in mathematics learning with equivalent fraction material. In this study using the type of Pre-Experimental Design with a research design that is One-Group-Pretest-Posttest Design. The population in this study were all fourth grade students at SDN 044/VIII Teluk Singkawang with a total of 22 students. The results of the observation data were calculated and compared based on the criteria with the normality test and hypothesis testing using the SPSS 20 application at a level of 0.05. Based on the results of hypothesis testing from the Wilcoxon Nonparametric test, a significant result was obtained of 0.018. Because the significant value obtained is 0.018 <0.05, the results of the Wilcoxon Nonparametric test can be concluded that Ho is rejected and Ha is accepted, so the researcher can conclude that there is a significant influence on the application of problem-based learning models to learning outcomes in mathematics on fractional material equivalent to class IV SDN 044/VIII Singkawang Bay.